Defining the "Tipping Point" to Success as a Surgeon–scientist: An Analysis of Applicants and Awardees of the American College of Surgeons Jacobson Promising Investigator Award. Issue 5 (7th May 2022) - Emamaullee, Juliet; Lian, Tiffany; Moroz, Stacy; Zuckerbraun, Brian; Matthews, Jeffrey; Gosain, Ankush
Abstract : Background: Since 2005, the American College of Surgeons has administered the Jacobson Promising Investigator Award (JPIA), which recognizes surgeon-scientists at the "tipping point" of their research careers. Objective: We retrospectively reviewed JPIA applicants to identify factors associated with selection for the award and future research success. Methods: Profiles were reviewed for all applicants between 2008 and 2018, at the time of application and as of 2019. Web of Science and NIH Reporter metrics were also reviewed for each applicant. Results: Eleven of 97 applicants were selected for the JPIA. At the time of application, awardees were more likely to have extramural (NIH K-award) versus intramural (KL2) or other career development award funding (55% vs 33%, P = 0.03) and more publications [median 70 (interquartile range, IQR 55–100) vs 40 (IQR 22–67), P = 0.03]. Post-application, JPIA awardees were more likely to achieve a higher h -Index and m-quotient compared to nonawardees ( P < 0.001 for both). All JPIA recipients received new NIH funding post-award, including 82% with R01 funding, compared to 23% of nonselected applicants ( P < 0.0001). Over $48 million from NIH was awarded to JPIA recipients since 2008, representing a 147-fold return on investment. Conclusions: Selection for the JPIA is associated with previous extramural NIH K award and, on average, 70 peer-reviewed publications at the time of application. Receipt of the JPIA is associated with a high rate of subsequent NIH R01 funding and publication metrics. The JPIA is an excellent indicator of "tipping point" success in academic surgery and demonstrates the huge potential impact of philanthropic support on early career surgeon-investigators.